Enhancing Moral Reasoning and Engagement in Islamic Education: A Constructivist Intervention in Aqidah and Akhlak - Marzuki, Marzuki; Hatta, Muhammad; Connaidi, Connaidi (FKIP Universitas Lampung, 2025)
Enhancing Moral Reasoning and Engagement in Islamic Education: A Constructivist Intervention in Aqidah and Akhlak. Objectives: This study aimed to investigate the effects of constructivist teaching approaches on students’ engagement and moral reasoning in Aqidah and Akhlak (Islamic creed and morality). It sought to determine whether constructivist-based learning could foster active participation, critical reflection, and ethical awareness among students compared to conventional teacher-centered instruction. Methods: The research employed a quasi-experimental design involving two classes of 30 students each. The experimental group was taught using constructivist methods, including collaborative learning, inquiry-based instruction, and moral case studies. In contrast, the control group received traditional instruction focused on direct explanation and memorization. Data were collected through pre- and posttests using the Student Engagement Scale and the Moral Reasoning Test. Statistical analysis, including paired and independent t-tests and ANCOVA, was conducted using SPSS version 27. Findings: The study results revealed that the experimental group experienced a significant improvement in engagement and moral reasoning compared to the control group. Posttest scores indicated increased student engagement and moral reasoning, demonstrating that constructivist approaches effectively enhanced students’ behavioral, emotional, and cognitive engagement, as well as their ability to reason about moral dilemmas grounded in Islamic values. Conclusion: Constructivist teaching strategies significantly improved both student engagement and moral reasoning in Islamic education. This study highlights the importance of integrating modern pedagogical approaches with Islamic educational principles to promote active learning and spiritual and moral development. Keywords: constructivist learning, aqidah and akhlak, student engagement, moral reasoning, islamic education.